ESBL-Positive Enterobacteriaceae from Dogs of Santiago and Boa Vista Islands, Cape Verde: A Public Health Concern - Alice Matos; Eva Cunha; Lara Baptista; Luís Tavares; Manuela Oliveira (MDPI AG, 2023)
Antimicrobial resistance is a public health threat with an increasing expression in low- and middle-income countries such as Cape Verde. In this country, there is an overpopulation of dogs, which may facilitate the spread of resistant bacteria, including extended-spectrum β-lactamase (ESBL)-producing Enterobacteriaceae. To clarify the role of dogs as reservoirs for the dissemination of this bacterial group, 100 rectal swab samples were collected from confined (n = 50) and non-confined (n = 50) dogs in Santiago and Boa Vista Islands, Cape Verde. These were analyzed using conventional bacteriological techniques for the detection of ESBL-producing Enterobacteriaceae and characterization of their pathogenic and resistance profiles. Twenty-nine samples displayed ESBL-positive bacteria, from which 48 ESBL-producing isolates were obtained and mostly identified as Escherichia coli. Multiple antimicrobial resistance indexes ranged from 0.18 to 0.70 and half of the isolates were classified as multidrug-resistant. Isolates were capable of producing relevant virulence factors, including biofilm, showing virulence indexes between 0.29 and 0.71. As such, dogs in Cape Verde may act as reservoirs of resistant bacteria, including pathogenic and zoonotic species, representing a public health concern. Although further investigation is needed, this study proposes the periodical analysis of dogs' fecal samples to monitor resistance dissemination in the country, in a One-Health perspective.